Enhancing Understanding of AI-Based Digital Business Through Interactive Seminars for Information Technology Students - Ade Sarah Huzaifah; Rossy Nurhasanah; Fanindia Purnamasari; Dedy Arisandi; Ivan Jaya (Indo Publishing, 2025)
The development of artificial intelligence (AI) technology has become a major driver in the transformation of the digital business world, including in the startup sector. However, a deep understanding of AI integration into business models remains a challenge for students, particularly in the field of Information Technology (IT). This community service activity aims to enhance the knowledge and skills of IT students in designing strategic, ethical, and sustainable AI-based digital businesses. The implementation method involves a one-day educational seminar, including presentations, interactive discussions, simulations of Business Model Canvas (BMC) development, and evaluation through questionnaires. Evaluation results showed significant improvements: understanding of the BMC increased from 41% to 89%, understanding of AI startup concepts from 54% to 92%, ability to draft a business plan from 16% to 78%, and motivation for technology entrepreneurship from 68% to 90%. These findings indicate that an applied and participatory approach in seminars is effective in developing digital entrepreneurship capacity among IT students.